Vertical Conflict on Regional Autonomy between the Regent of the Meranti Islands and the Governor of Riau and the Ministry of Finance - Tinanto, Bherry; Irawati, Irawati; Valentina, Tengku Rika (ARISTO, 2024)
In the process of implementing regional autonomy, conflict is inevitable. Internal disputes between autonomous areas, vertical conflicts between autonomous regions, and horizontal conflicts between autonomous regions are the three categories of conflicts involving regional autonomy. This study examines uncommon vertical disputes in autonomous territories, namely the dispute between the Ministry of Finance, the Governor of Riau, and the Regent of the Meranti Islands. The purpose of this study is to elucidate the mechanisms behind conflict, including its origins and ways to resolve it. The study's findings suggest that the very little fiscal support given to the Meranti Islands Regency Government is what triggers the conflict process, which starts with interaction. Special Financial Assistance (BKK) is budget support from the provincial government of Riau, whereas Profit Sharing Funds (DBH) are budget support from the federal government. Limited resources, such as a tiny APBD, regional poverty, and a large number of unemployed people who migrate to neighboring countries as migrant laborers are the root causes of this conflict. The divergent objectives of the Ministry of Finance, the Governor of Riau, and the Regent of the Meranti Islands constitute the second cause of conflict. The Governor believes that funds will be distributed based on statistics and indicators, the Regent wants to deliver as much funding as possible to the regions, and the Ministry of Finance considers financial equality across the area. The third source of conflict is miscommunication, which includes spreading the word through the media and making diabolical remarks in public forums directed at the Ministry of Finance. The personality of the Meranti Islands Regent, who exudes a spectacular and haughty demeanor while leading the government, is the fourth point of contention. The final methods of resolving conflicts are negotiation and mediation.